2016
DOI: 10.1186/s12915-016-0228-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of plant immune receptor architectures uncovers host proteins likely targeted by pathogens

Abstract: BackgroundPlants deploy immune receptors to detect pathogen-derived molecules and initiate defense responses. Intracellular plant immune receptors called nucleotide-binding leucine-rich repeat (NLR) proteins contain a central nucleotide-binding (NB) domain followed by a series of leucine-rich repeats (LRRs), and are key initiators of plant defense responses. However, recent studies demonstrated that NLRs with non-canonical domain architectures play an important role in plant immunity. These composite immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
369
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(386 citation statements)
references
References 78 publications
14
369
0
3
Order By: Relevance
“…A previous survey (Cesari et al, 2014) revealed similar and unique integrated domain fusions to LRR-containing proteins, commonly occurred in mosses and across numerous lineages of flowering plants, enabling by this way an efficient fungal recognition. According to Sarris et al, (2016) the most abundant group of domains fusions at LRR-containing proteins is involving the kinase domain found in receptor-like kinases that transducer PAMPtriggered immunity in plants; these findings are in line with our results, as such integrated domains were quite frequent in our M. notabilis LRR-RSTK dataset. The primary genomic assembly of M. notabilis (He et al, 2013) does not include any assembled chromosomes or linkage groups (Li et al, 2014), hence we could not test whether these genes are found at tandem clusters.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A previous survey (Cesari et al, 2014) revealed similar and unique integrated domain fusions to LRR-containing proteins, commonly occurred in mosses and across numerous lineages of flowering plants, enabling by this way an efficient fungal recognition. According to Sarris et al, (2016) the most abundant group of domains fusions at LRR-containing proteins is involving the kinase domain found in receptor-like kinases that transducer PAMPtriggered immunity in plants; these findings are in line with our results, as such integrated domains were quite frequent in our M. notabilis LRR-RSTK dataset. The primary genomic assembly of M. notabilis (He et al, 2013) does not include any assembled chromosomes or linkage groups (Li et al, 2014), hence we could not test whether these genes are found at tandem clusters.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, we observed evidence of various functional domains fusions, predominantly at the C-termini of M. notabilis LRR-RSTKs, mostly integrated by the Pkinase_Tyr and the Malectin or Malectin-like domains. Recent studies demonstrated that LRR-containing proteins with non-typical domain architectures, mainly these that are including "integrated decoys", play a crucial role in plant immunity with an integration re-occurring and an evolutionarily conserved pattern being evident across numerous species lineages (Sarris et al, 2016). A previous survey (Cesari et al, 2014) revealed similar and unique integrated domain fusions to LRR-containing proteins, commonly occurred in mosses and across numerous lineages of flowering plants, enabling by this way an efficient fungal recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The most common domains match known integrated decoy domains 85,86 , but many more rare types were also found. The presence of specific domains in different NLR subfamilies point to multiple, independent acquisitions of decoys by NLRs (Supplementary Table 42).…”
Section: −6mentioning
confidence: 99%
“…Given that the HvWRKY1/2 and MYB6 transcription factors interact with the MLA10 CC domain (20,45), it is possible that these nuclear proteins are guardees/decoys that are necessary for effector perception. Indeed, recent findings suggest that transcription factors such as WRKY and MYB are common integrated domains/decoys in plant NLR proteins, indicating that they could be common effector targets (46)(47)(48). Previous yeast two-hybrid assays did not detect any interaction of the Sr33 CC domain with HvWRKY1, HvWRKY2, or their wheat orthologs (10).…”
Section: Discussionmentioning
confidence: 99%